2002
DOI: 10.1046/j.1469-0691.2002.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications in patients undergoing unrelated donor bone marrow transplantation: experience from a single institution

Abstract: A high incidence of life-threatening infections and infection-related mortality was observed. A high rate of CMV infection in the early period, and death caused by multiresistant Gram-negative microorganisms in the late period, were the main findings in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…Half of all infectious complications occur during the first 4-6 weeks following hematopoietic grafting, and most of them are bacterial in origin. [1][2][3][4] In spite of prophylaxis with oral antibiotics (mainly fluoroquinolones) used by some groups, most of the patients (90-100%) who receive myeloablative hematopoietic transplantation develop fever 22 and need initiating empirical antibiotic therapy that usually continues until neutropenia resolves. The use of empirical intravenous antibiotic therapy may actually prevent subsequent infections as reported in some studies by Table 3 Pathogens isolated in patients with bacteremia during FFE, according to treatment group All patients Study group patients (Pip-Tazo) Control group patients (Quinolone)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of all infectious complications occur during the first 4-6 weeks following hematopoietic grafting, and most of them are bacterial in origin. [1][2][3][4] In spite of prophylaxis with oral antibiotics (mainly fluoroquinolones) used by some groups, most of the patients (90-100%) who receive myeloablative hematopoietic transplantation develop fever 22 and need initiating empirical antibiotic therapy that usually continues until neutropenia resolves. The use of empirical intravenous antibiotic therapy may actually prevent subsequent infections as reported in some studies by Table 3 Pathogens isolated in patients with bacteremia during FFE, according to treatment group All patients Study group patients (Pip-Tazo) Control group patients (Quinolone)…”
Section: Discussionmentioning
confidence: 99%
“…1 In spite of the reduction in post transplant aplasia associated with the use of peripheral blood stem cells and myeloid growth factors, more than 80% of patients develop fever and infections that are the leading cause of transplant-related mortality (TRM). [2][3][4] The most frequent approach to reducing the incidence of infection is the administration of oral antibiotic regimens, which aim to eliminate aerobic bacteria while maintaining colonization resistance by preserving the anaerobic flora. [5][6][7] In neutropenic patients, antibacterial chemoprophylaxis with fluorinated quinolones has reduced the incidence of Gram negative bacteremia.…”
mentioning
confidence: 99%
“…Ten patients (37%) died prior to day 100. Infection was a direct cause of death in 4 patients [74]. Investigators from Japan reported cytomegalovirus (CMV) infection following UCB in 28 adults compared with sibling matched (R-BMT) and URD BM recipients.…”
Section: Ucb Basic Biology and Implications For Immune Reconstitutionmentioning
confidence: 99%
“…7 Third, allogeneic HSCT requires post-HSCT pharmacologic immunosuppression. The ensuing immunodeficient state renders HSCT recipients particularly susceptible to opportunistic infections that require T-cell control, such as caused by viruses [8][9][10][11] and fungi. 12 The profound alteration of T-cell immunity thus represents a still-unsolved core problem of HSCT (reviewed in Storek and Witherspoon 13 ).…”
Section: Introductionmentioning
confidence: 99%